Simple apparatus to measure Seebeck coefficient up to 900 K. (May 2015) - Mishra, Avinna; Bhattacharjee, Sarama; Anwar, Shahid
Graphical abstract: Highlights: Simple Seebeck ( S ) coefficient measurement setup without any tailor made probes. Able to measure S from room temperature to 900 K in air. The measured S values has fair reproducibility with standard deviation Δ S  ± 5 μV/K. Error in S values of the order of 2–3% till 600 K, increases to 5–7% at 900 K. User friendly setup for measurement of S values for small bulk samples. Abstract: An apparatus for measuring Seebeck coefficient ( S ) has been designed that allows measurement of S from room temperature to 900 K. It is constructed from readily available equipment and instrumentation with parts that can be easily fabricated. The details of instrument fabrication, sources of errors, method of calibration, typical measurement in test sample are described. We report the Seebeck coefficient measurement of Ca-cobaltite (Ca3 Co4 O9 ) a p-type thermoelectric material. The obtained results from the fabricated setup are well matched with the reported and standard instrument data with standard deviation of ±3%.